Effects of biochars on the fate of acetochlor in soil and on its uptake in maize seedling. (October 2018) - Li, Yao; Liu, Xingang; Wu, Xiaohu; Dong, Fengshou; Xu, Jun; Pan, Xinglu; Zheng, Yongquan
Abstract: Biochar (BC) can alter the fate and bioavailability of pesticides in soil. In this study, the effects of three types of BCs (made of crofton weed, wood chips and rice hull) on the sorption of acetochlor, a common herbicide, were investigated. The acetochlor sorption constants ( K f value) were 309.96 μg 1−n L n/ kg (biochars made of ricehull, BCR), 3.54 μg 1−n L n/ kg (biochars made of crofton weed, BCH) and 2.27 μg 1−n L n/ kg (biochars made of wood chips, BCW). The persistence of acetochlor was 8 times greater when 1% BCR was added to the soil. Moreover, the half-life of acetochlor increased with increasing amounts of BC in the soil. The soil was amended with BCH (made of crofton weed) for two different aging period (10 d and 20 d) to evaluate the effects of aged BC on acetochlor accumulation in maize seedlings ( Zea mays L ). Amendment with 10 d-aged BCH in soil decreased the bioaccumulation of acetochlor. However, the concentrations and bioconcentration factors in maize cultivated in 20 d-aged BCH-amended soils were significantly higher than those in soil with no BCH amendments and with 10 d-aged BCH amendments. These results imply that BC aged in soil for a long period can increase the bioaccumulation of acetochlor in plants and the influences of BC on environmental risks of pesticides must be further clarified. Graphical abstract: Highlights: Biochar can extend the persistence of acetochlor in soil. Root was the main enrichment site of acetochlor in plants. 20 d-aged BC reduced the BCF of acetochlor in plants. 20 d-aged BC enhanced the BCF of acetochlor in plants compared with 10 d-aged BC.